The Influence of Supervision and Managerial Skills of School Principals on Teacher Performance at SDN 43 Mandau - Yenteti, Filda; Indra, Musnar; Aditya, Aditya (Journal of English Language and Education, 2025)
This study aims to determine the effect of principal supervision and managerial skills on teacher performance at SDN 43 Mandau. The method used is a quantitative approach with multiple linear regression analysis techniques assisted by the SPSS program. The population in this study were 15 teachers at SDN 43 Mandau, sampling was carried out using the total sampling technique. Data were collected through questionnaires distributed to 15 teachers, consisting of 10 statement items for the principal supervision variable, 15 statement items for the principal managerial skills variable, and observation sheets for the teacher performance variable. The results showed that principal supervision had a significant effect on teacher performance with a significance value of 0.038 0.05. Likewise, the principal's managerial skills showed a significant effect on teacher performance with a significance value of 0.013 0.05. Simultaneously, both variables had a significant effect on teacher performance with a significance value of 0.001 0.05. Thus, it can be concluded that principal supervision and managerial skills partially and simultaneously have an effect on improving teacher performance. Based on these results, it can be concluded that the better the principal's supervision and managerial skills, the higher the teacher's performance. The implication of this study is the need to strengthen the principal's capacity in the supervisory and managerial aspects as a strategic effort to improve the quality of learning and teacher professionalism in elementary schools.